Determination of the Elastic Constant of the Top Plate of a Cello in the Interaction with the Bridge - Pablo PAUPY; Pablo TABLA; Dario HUGGENBERGER; Federico ELFI; Eneas N. MOREL; Jorge R. TORGA (Archives of Acoustics)
This paper aims to determine the equivalent static elastic constant of a cello’s top plate in the interaction with the bridge. Experimental results detailing this constant are presented based on measuring the deformation and forces caused by a system of calibrated springs in similar conditions to that obtained when these forces are produced by the action of the strings. Subsequent tests are conducted following an intervention by a luthier to adjust the sound post, with the aim of assessing the impact on the elastic constants.